Multi-Agent System (MAS) for short-term generation scheduling of a microgrid - Logenthiran, T; Srinivasan, D; Khambadkone, A M; Aung, H N (2010 IEEE International Conference on Sustainable Energy Technologies (ICSET), 2010)
Microgrids are low voltage distribution networks comprising various distributed generators, storage devices and controllable loads. Microgrid can be operated in interconnected mode or islanded mode. Optimal generation scheduling is one of the microgrid energy management system's function for optimizing the microgrid operation. This paper presents a Multi-Agent System (MAS) for generation scheduling of a microgrid. The proposed MAS architecture has different types of agents such as micro source controller agent, load controller agent, storage agent, and microgrid controller agent. Micro source controller agent that models corresponding distributed energy source such as photovoltaic, wind turbine and distributed generators, maximizes its power production subject to production cost and unit's constraints. Load controller agent that represents corresponding controllable load in the system, is capable to do demand side management techniques. The main goal of this paper is to develop a distributed MAS for generation scheduling and monitoring of energy resources for optimized microgrid operation. The MAS was successfully developed in JADE, which is a well-known FIPA compliant open source multi-agent platform.